THE INFLUENCE OF DEEP BREATHING RELAXATION TECHNIQUES TO DECREASE PAIN LEVELS IN THE MOTHERS INPARTU ACTIVE PHASE OF THE FIRST STAGE AT KERTHA USADA HOSPITAL SINGARAJA - Pratiwi, Putu Irma; Damayanti, Dina Sulviana; Petricka, Grace (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Pain is the bodys defense mechanism which is unpleasant. Deep breathing relaxation technique is one of the non-pharmacological methods to relieve the pain felt by the mother during labor. Aims: The purpose of this study was to determine the effect of deep breathing relaxation techniques to decrease the level of pain in the first stage the mother inpartu active phase. Methodology: Pre Experimental Research. The design of this study used one-group pre-test- posttest design. The measurement of pain is done twice: before the experiment and after the experiment. The sampling technique in this research is total sampling method. The instrument used to measure the level of pain is a Visual Analog Scale (VAS). Giving intervention such as deep breathing relaxation techniques during the active phase of the first stage of contraction repeatedly from the start to the end of the contraction contractions performed during 10 cycles of contraction. Results: the results of measuring the degree of pain the mother inpartu active phase of the first stage before being given a breath relaxation techniques in 30 respondents are located mainly in the category of severe pain as many as 19 people (63.30%). Conclusion: deep breathing relaxation technique is one of the non-pharmacological techniques are most useful to treat pain by regulating the breath, with attention to respiratory expected conditions to be relaxed so that the mother can reduce pain.Â